1961
DOI: 10.1083/jcb.11.3.724
|View full text |Cite
|
Sign up to set email alerts
|

Corpus Intra Cristam: A Dense Body Within Mitochondria of Cells in Hyperplastic Mouse Epidermis

Abstract: This communication reports the occurrence of dense bodies within the eristaO of many mitochondria in the stratum germinativum and stratum granulosum of hyperplastie mouse epidermis. We have seen a variety of forms which suggest that these intramitochondrial bodies may be related to the so called keratohyaline granules of skin seen in the light microscope. A similar finding has been reported previously from electron micro-1 The transverse lamellae of mitochondria appear in thin sections as two parallel dense li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
11
0

Year Published

1962
1962
1995
1995

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 15 publications
(10 reference statements)
4
11
0
Order By: Relevance
“…The st. corneum appears to show persistent lipid vesicles, an ultrastructural feature which has been previously reported in psoriatic epidermis (37). Mitochondrial aberrations similar to the ones which we observed in the fsn/fsn mice have been previously reported in hyperplastic mouse epidermis (38). Those authors suggested that they represented keratohyalin granules which continue to grow causing eventual dissolution of mitochondrial function (38).…”
Section: Discussionsupporting
confidence: 86%
“…The st. corneum appears to show persistent lipid vesicles, an ultrastructural feature which has been previously reported in psoriatic epidermis (37). Mitochondrial aberrations similar to the ones which we observed in the fsn/fsn mice have been previously reported in hyperplastic mouse epidermis (38). Those authors suggested that they represented keratohyalin granules which continue to grow causing eventual dissolution of mitochondrial function (38).…”
Section: Discussionsupporting
confidence: 86%
“…Several other investigators observed inclusions within keratinocyte mitochondria. A 1961 report describes mitochondrial inclusions in mouse epidermis made hyperplastic by the application of croton oil (15). The inclusions were termed "corpus intra cristam" and were considered to be involved in the formation of keratohyaline granules even though they were not demonstrated in normal mouse skin.…”
Section: Mitochondrial Inclusions In Keratinocytesmentioning
confidence: 99%
“…Large internal bodies surrounded bv a halo were observed in mitochondria of Aconthonzoebo during cncvstationebv Viclterman (1960). Frei and Sheldon ( 1961) also discovered similar bodies in mitochondria in mouse e~idermal cells in resDonse to treatment with carcino-1 1 gens. In both instances.…”
mentioning
confidence: 89%